2011
DOI: 10.4055/cios.2011.3.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Acetabular Posterior Wall Fractures

Abstract: BackgroundThe results after acetabular fracture are primarily related to the quality of the articular reduction. We evaluated the results of internal fixation of posterior wall fractures with using three-step reconstruction.MethodsThirty-three patients (mean age at the time of injury, 47.9 years; 28 males and 5 females) were followed for a minimum of 2 years after surgery. The three-step reconstruction included 1) preservation of soft tissues and reduction of the marginally impacted osteochondral (articular) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 28 publications
2
38
0
5
Order By: Relevance
“…However surgical approach is not fixed, the reduction is more difficult and the overall clinical results are known to be worse than simpler fracture patterns [25] [26] [27]. Displacement of the fragmented bones leads to articular incongruity of hip joint, distribution on the articular surface which leads to arthritis of joint [28]. The main goal of treatment of acetabulum fracture is to return the patient to normal functional level and to daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…However surgical approach is not fixed, the reduction is more difficult and the overall clinical results are known to be worse than simpler fracture patterns [25] [26] [27]. Displacement of the fragmented bones leads to articular incongruity of hip joint, distribution on the articular surface which leads to arthritis of joint [28]. The main goal of treatment of acetabulum fracture is to return the patient to normal functional level and to daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…2 Kim et al reported reconstruction of acetabular posterior wall fractures, in this series of 33 patient 26 had road traffic accidents, 5 had fall from height, 2 had sport related trauma. 3 In the present series out of 30 patients 28 had road traffic accidents, 2 had fall from height, the most common mode of trauma was RTA in 28 (93%). The results were found similar to previous studies.…”
Section: Mode Of Traumamentioning
confidence: 99%
“…3 Lim et al described operative treatment of acetabular fractures, in this series most of the cases 14 out of 23 involved posterior wall fractures. 5 In our present series posterior wall fractures were seen in 26 (87%) of patients and posterior column fractures were seen in 4 (13%) of cases.…”
Section: Type Of Fracturesmentioning
confidence: 99%
See 2 more Smart Citations